A STUDY OF ACCOUNTING CURRICULA. - Maxwell, Arthur D.; Taylor, W. Howard (The Accounting Review, 1942)
During 1940 the Curriculum Committee and the members of the Accounting Department of the Wharton School of Finance and Commerce, University of Pennsylvania, Philadelphia, Pennsylvania, made a study of the accounting curriculum to determine if it needed revision. As an aid in this study, two questionnaires were sent out, one to the Deans of the fifty-two other schools in the Association of Collegiate Schools of Business, and the other to 494 graduates in accounting. The answers received to these questionnaires were informative and helpful to the Committee and to the Department. With the thought that the data might be of interest to others this analysis and summary of the answers to the questions has been prepared. The replies of the graduates are considered first. As a result of the questionnaires sent to the graduates and to the schools, and the recommendations of the Accounting Department to the Curriculum Committee, the Faculty of the Wharton School of Finance and Commerce approved a new accounting curriculum. The new curriculum increases the semester credits offered in accounting from 31 to 39.